Continuous Glucose Monitoring for Glycemic Control in Children and Adolescents Diagnosed with Diabetes Type 1: A Systematic Review and Meta-Analysis - Dorando, Elena; Haak, Thomas; Pieper, Dawid (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aim The aim of this meta-analysis was to evaluate the impact of continuous glucose monitoring (CGM) systems on short- and long-term glycemic control in children and adolescents diagnosed with diabetes type 1.Methods The review was registered in PROSPERO (CRD42019135152). We partly updated a formerly published systematic review and searched several databases (Ovid MEDLINE, Embase, CENTRAL, and Clinicaltrials.gov) in May 2019. Summary measures were estimated as relative risks (RR) and standardized mean differences (SMD). The primary endpoint of our analysis was frequency of hypoglycemic events. Quality of evidence was evaluated using the GRADE approach.Results Eleven studies with a total number of 818 patients were included in our review. Meta-analyses indicated a potential benefit of CGM systems regarding the relative risk of a severe hypoglycemic event (RR 0.78; 95% CI 0.29 to 2.04) and mean level of HbA1c at end of study (SMD -0.23; 95% CI -0.46 to 0.00). Certainty of evidence for effect estimates of these meta-analyses was low due to risk of selection bias and imprecision of the included studies. Qualitative analyses of the secondary outcomes of user satisfaction and long-term development of blood glucose supported these findings.Conclusion CGM systems may improve glycemic control in children and adolescents diagnosed with diabetes type 1, but the imprecision of effects is still a problem. Only a few studies examined and reported data for pediatric populations in sufficient detail. Further research is needed to clarify advantages and disadvantages of CGM systems in children and adolescents.
Keywords: CGM; hypoglycemic event; pediatrics